1967
DOI: 10.1136/bmj.2.5550.507-d
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronidase in the Treatment of Allergy

Abstract: BRIrTH 507 of a needle pick it out. It is the simplest of procedures: the mite clings to the point of the needle, it can be placed on a slide, and its lively antics watched with great amusement under the microscope. This technique takes no more than a few minutes to master and yet I rarely see it practised. It is most impressive to teacher, student, nurse, and patient, and serves good purpose. The problem is quite different for the management of that very rare variety called Norwegian, or crusted, scabies of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1970
1970
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…The present results give experimental support to the suggestion of McEwen et al [1967] that the ability of commercial samples of hyaluronidase to potentiate clinical hyposensitisation depends on their con tamination with different quantities of /3-glucuronidase.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The present results give experimental support to the suggestion of McEwen et al [1967] that the ability of commercial samples of hyaluronidase to potentiate clinical hyposensitisation depends on their con tamination with different quantities of /3-glucuronidase.…”
Section: Discussionsupporting
confidence: 77%
“…In an earlier study [McEwen et al, 1967], it was reported that pa tients who had specific allergic diseases of the immediate type were considerably improved by the application of a mixture of hyaluronidase and specific antigen to a scarification site on the forearm. The sample of hyaluronidase used in this study was found to be contaminated with a variable mixture of enzymes, and one of these, /9-glucuronidase, was shown to confer the beneficial therapeutic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Following the discovery of the method during clinical work [62], and a preliminary unpublished successful double-blind clinical trial in 1967, further detailed development was conducted in experimental animals [63-71. This led to identification of the critical dose range for allergens in the treatment, and of the significance of specific adjunctive chemicals, of which the two mentioned above are the most important. A double-blind verification of the work in hay fever sufferers was conducted [67], and a further small study in food allergy sufferers reported a successful outcome in 1975 [68].…”
Section: Enzyme Potentiated Desensitizationmentioning
confidence: 99%
“…Of these, 26 received the 'very sensitive' grade (a total of 4,800 Protein Nitrogen Units), 10 received the 'moderately sensitive' grade (9,570 PNU total) and six were given the 'mildly sensitive' injections (20,650 PNU total). Ten other control patients were administer ed single placebo injections of 0.9% saline in a depot form [M c Ew en , G anderton, W ilson and Black, 1967].…”
Section: Methodsmentioning
confidence: 99%